Delay jitter bounds and packet scale rate guarantee for expedited forwarding - Bennett, J.C.R.; Benson, K.; Charny, A.; Courtney, W.F.; Le Boudec, J.-Y. (IEEE/ACM transactions on networking, 2002)
We consider the definition of the expedited forwarding per-hop behavior (EF PHB) as given in RFC 2598 and its impact on worst case end-to-end delay jitter. On the one hand, the definition in RFC 2598 can be used to predict extremely low end-to-end delay jitter, independent of the network scale. On the other hand, the worst case delay jitter can be made arbitrarily large, while each flow traverses at most a specified number of hops, if we allow networks to become arbitrarily large; this is in contradiction with the previous statement. We analyze where the contradiction originates and find the explanation. It resides in the fact that the definition in RFC 2598 is not easily implementable in known schedulers, mainly because it is not formal enough and also because it does not contain an error term. We propose a new definition for the EF PHB, called "packet scale rate guarantee" (PSRG) that preserves the spirit of RFC 2598 while allowing a number of reasonable implementations and has very useful properties for per-node and end-to-end network engineering. We show that this definition implies a rate-latency service curve property. We also show that it is equivalent, in some sense, to the stronger concept of "adaptive service guarantee". Then we propose some proven bounds on delay jitter for networks implementing this new definition in cases without loss and with loss.